2023
DOI: 10.1007/s11240-023-02560-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress hormones on the metabolome of a suspension culture of the aromatic medicinal plant Cymbopogon schoenanthus subsp. proximus

Abstract: The current study aimed to evaluate and compare the effect of different concentrations (0.0–200.0 µM) of jasmonic acid (JA), methyl jasmonate (MeJA), and salicylic acid (SA) on suspension culture mass production and untargeted metabolic profiling of the medicinal plant Cymbopogon schoenanthus subsp. proximus. The addition of 50 µM MeJA improved the fresh weight of embryogenic tissue significantly. MeJA and SA did not affect tissue dry weight, whereas JA significantly decreased it. Based on 1H and 1H–13C NMR da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Consistent with our results, another report mentioned that although both fructose and glucose were decomposition products of sucrose, glucose was utilized for monosaccharide metabolism in Salvia miltiorrhiza cells under prolonged exposure to the elicitor [ 50 ]. Another study also reported that asparagine metabolism was upregulated with 100 µM MeJA to activate the aminoacyl-tRNA biosynthesis pathway, which is a critical pathway in the plant stress response and is responsible for the attachment of amino acids such as asparagine and 4-aminobutyrate [ 51 ]. However, this pathway was dramatically decreased upon adding 200 µM MeJA as asparagine was altered to stimulate specialized metabolite production [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, another report mentioned that although both fructose and glucose were decomposition products of sucrose, glucose was utilized for monosaccharide metabolism in Salvia miltiorrhiza cells under prolonged exposure to the elicitor [ 50 ]. Another study also reported that asparagine metabolism was upregulated with 100 µM MeJA to activate the aminoacyl-tRNA biosynthesis pathway, which is a critical pathway in the plant stress response and is responsible for the attachment of amino acids such as asparagine and 4-aminobutyrate [ 51 ]. However, this pathway was dramatically decreased upon adding 200 µM MeJA as asparagine was altered to stimulate specialized metabolite production [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study also reported that asparagine metabolism was upregulated with 100 µM MeJA to activate the aminoacyl-tRNA biosynthesis pathway, which is a critical pathway in the plant stress response and is responsible for the attachment of amino acids such as asparagine and 4-aminobutyrate [ 51 ]. However, this pathway was dramatically decreased upon adding 200 µM MeJA as asparagine was altered to stimulate specialized metabolite production [ 51 ]. As 200 µM MeJA increased the accumulation of asparagine, which acts as an enzyme stimulator, quinic acid entered the phenylpropanoid pathway and was altered to other specialized metabolites [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%